Expanding the Civil Liability of Biological Fathers toward Children Born Out of Wedlock through Trust Fund Mechanisms - Azhar Rashed; Faisal Afda'u (Syekh Ali Hasan Ahmad Addary State Islamic University, 2026)
This research examines the expansion of the civil responsibility of biological fathers toward children born out of wedlock through the implementation of a trust fund mechanism. The primary objective is to analyze how legal instruments can guarantee the long-term welfare of illegitimate children beyond basic maintenance. This study utilizes a normative legal research method with a statutory and conceptual approach, analyzing the Constitutional Court Decision Number 46/PUU-VIII/2010. The findings indicate that while Indonesian law recognizes the civil relationship between a biological father and an illegitimate child, enforcement of financial support remains inconsistent. The introduction of a trust fund serves as a preventive and curative legal solution to ensure educational and healthcare sustainability. The study concludes that legislative reform is necessary to integrate trust fund principles into the Indonesian civil law system to provide better legal certainty and protection for the best interests of the child.